540 Post-offer/pre-employment screening for carpal tunnel syndrome and other musculoskeletal disorders: is it effective?. (24th April 2018) - Evanoff, BA; Buckner-Petty, S; Dale, AM
Abstract : Introduction: Pre-employment examinations, known as post-offer pre-placement (POPP) tests in the US, are performed by many US employers to prevent work-related musculoskeletal disorders (MSDs) such as carpal tunnel syndrome (CTS). However, there is no strong evidence of effectiveness of such screening. We tested the predictive validity of POPP screening using nerve conduction studies (NCS) to identify future cases of carpal tunnel syndrome (CTS) among manufacturing workers. Methods: We used data from a natural experiment in which 1648 newly hired production workers in a manufacturing plant underwent baseline physical exam and NCS, but were hired regardless of test results. Workers were then followed for up to 5 years; outcomes of CTS and workplace physical exposures in different jobs were obtained from the employer's medical and safety records. Results: There was no association between NCV results at the time of hire and future CTS. Varying the diagnostic cut-offs for determining 'abnormal' NCS did not improve predictive validity. However, workers in jobs with high hand/wrist exposure showed greater risk of CTS than those in low exposed jobs (Relative Risk 2.82; 95% CI: 1.52 to 5.22). Discussion: NCS and other screening tests for the musculoskeletal system are commonly used in the US as a primary means to reduce or prevent MSDs, despite little evidence that such testing predicts which workers will incur MSDs in the future. Ours is the third study to find that POPP screening is ineffective as a preventive strategy for CTS. Other common testing strategies for MSDs do not satisfy evidence-based criteria, and their use should be scrutinised. Such screening seems a poor use of health and safety resources, which could better be spent on improving work activities to reduce injury risk for the entire worker population.